An effective approach to improve the electrochemical performance of LiNi0.6Co0.2Mn0.2O2 cathode by an MOF-derived coating. Issue 16 (6th April 2016) - Li, Siwu; Fu, Xiaotao; Zhou, Junwen; Han, Yuzhen; Qi, Pengfei; Gao, Xing; Feng, Xiao; Wang, Bo
Abstract : We report an effective surface modification for NCM-622, using MOF-derived alumina (MDA) coatings. The coated NCM-622 shows greatly enhanced performance: 214.6 and 196.5 mA h g −1 at 0.2C and 1C, respectively, with capacity retention of 92.7% after 100 cycles at 1C. Abstract : Herein, we report an effective surface modification for a high energy cathode material, LiNi0.6 Co0.2 Mn0.2 O2 (NCM-622), using an Al-based MOF (NH2 -MIL-53), as a precursor to produce MOF-derived alumina (MDA) coatings. The MDA-coating (2.5 wt%) is well-dispersed on the surface of NCM-622 with an amorphous structure. By virtue of the MDA-coating, NCM-622 shows greatly enhanced electrochemical performance: 214.6 mA h g −1 and 196.5 mA h g −1 (3.0–4.5 V vs. Li + /Li) at 0.2C and 1C, respectively, with a capacity retention of 92.7% after 100 cycles at 1C; even at high rates of 5C and 10C, the discharge capacity still approaches 168.5 mA h g −1 and 150.0 mA h g −1, respectively. We found that these enhancements can be ascribed to the improved structural stability and electrochemical kinetics of NCM-622 by the MDA-coating.